How can we assess neuromuscular performance in female football players? A systematic review - Moreno-Ortega, C.; González-García, J.; Romero-Moraleda, B. (Scientific Journal of Sport and Performance, 2026)
Women's football has experienced exponential growth in popularity, leading to a notable improvement in player performance and an increased interest in optimizing player development. This systematic review aimed to identify the most frequently used tests for evaluating neuromuscular performance in female football players. In accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, we conducted a systematic search of the literature using keywords related to football, neuromuscular training, and measurement methods. The literature search yielded 109 articles (PubMed = 27; WoS = 31; Scopus = 32; SportDiscus = 19). After screening, 19 articles met the inclusion criteria and were thoroughly reviewed. The most commonly assessed variables in neuromuscular testing included jump ability, agility, sprinting, fitness, strength, and balance. The wide variety of tests used for each skill, coupled with a lack of standardized methodologies, hinders the establishment of robust recommendations. Consequently, further research is necessary to evaluate the validity of these tests and to develop an appropriate battery of neuromuscular assessments.